1993
DOI: 10.1063/1.466100
|View full text |Cite
|
Sign up to set email alerts
|

Free surfaces of polymer blends. II. Effects of molecular weight and applications to asymmetric polymer blends

Abstract: The composition of the free surface of a binary polymer blend has been investigated in this work as a function of molecular weights, energetic parameters, and composition. The approach involved the use of a compressible mean-field lattice model that was developed in the spirit of the Scheutjens and Fleer theory of polymer solutions [J. Chem. Phys. 98, 6516 (1993)]. For symmetric polymer blends it was found that the surface segregation was driven by the degree of incompatibility of the blend, with the segregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…Thus, the patchy PS overlayer may be due to partial surface aggregation from short PS 6 chains. Such surface aggregation of short chains in our system is similar to the segregation behavior of short chains in a binary mixture of two homopolymers with different molecular weights [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 60%
“…Thus, the patchy PS overlayer may be due to partial surface aggregation from short PS 6 chains. Such surface aggregation of short chains in our system is similar to the segregation behavior of short chains in a binary mixture of two homopolymers with different molecular weights [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 60%
“…ratio). 24 For a binary blend of polymers with disparate molecular weights, Hariharan et al 61 showed that entropic effect would drive the low-M w component to the film surface, producing a local enrichment of the low-M w component. Thus, one expects the 13.7 K constituent in the blend films to segregate to the surface.…”
Section: Effect Of Chain Endsmentioning
confidence: 99%
“…Hariharan et al (16,19,23,24) conducted mean-field Scheutjens-Fleer calculations for the surface segregation from miscible polymer mixtures. They considered the segregation to both neutral hard surfaces, and to the free air surface.…”
Section: Numerical Verificationmentioning
confidence: 99%